Comparative Analysis of Robot-Assisted versus Traditional Laparoscopic Retroperitoneal Partial Nephrectomy - Sahin Kilic; Enis Mert Yorulmaz; Çağatay Özsoy; Murat Sambel; Yigit Akın; Mutlu Ateş (Van Tıp Dergisi)
INTRODUCTION: This study aimed to assess the effectiveness of laparoscopic retroperitoneal partial nephrectomy (LRPN) and robot-assisted retroperitoneal partial nephrectomy (RRPN) in managing renal tumors, with a focus on perioperative efficiency, oncological safety, and preservation of renal function.